Films as a means of social and emotional learning in higher education - Duzhyk, Nataliia (My University, 2019)
Integration of social and emotional learning into the education process has been one of the most popular international trends for over 20 years. Using film episodes is an effective tool of expanding students’ vocabulary and practicing the English language with a greater confidence and precision. This enables students to develop emotional sensitivity and conflict resolution skills, to display a socially cultivated behavior and learn advanced communication practices. Соціально-емоційние навчання є однією з найбільш популярних освітніх технологій, яка використовуєтся у різних країнах понад 20 років. Використання епізодів із художніх фільмів дозволяє збільшувати словниковий запас студентів, а також послуговуватися англійською мовою більш упевнено та точно. Цей підхід уможливлює розвиток емоційного інтелекту, уміння долати конфліктні ситуації, засвоювати норми соціально прийнятної поведінки, а також новітні комунікативні стандарти.
Keywords: емоційне навчання; teaching a foreign language; викладання іноземної мови; emotional intelligence; кафедра ділової іноземної мови та міжнародної комунікації